Model Game Based Learning Berbantuan Media Flash Card dalam Pembelajaran Bahasa Indonesia Terhadap Hasil Belajar Kognitif dan Keterampilan Menulis Permulaan Siswa Kelas I SD Negeri 86 Kota Bengkulu - Kartini; Muktadir, Abdul; Gumono (UNIB Press, 2025)
This study investigates the effect of the Game-Based Learning (GBL) model assisted by flashcard media on the cognitive learning outcomes and early writing skills of first-grade students at SD Negeri 86 Bengkulu City. The research employed a quasi-experimental method with a pretest-posttest control group design, involving two classes: IA (experimental) and IB (control), each with 20 students. Data were collected through observation, tests, and documentation, and analyzed using the t-test. The findings show that the use of the Game-Based Learning model with flashcard media significantly improved students’ cognitive learning outcomes and early writing skills. The model made the Indonesian language learning process more interactive, engaging, and effective.